Ammonothermal Synthesis of Ba2PO3N – An Oxonitridophosphate with Non‐Condensed PO3N Tetrahedra. Issue 10 (26th February 2020) - Wendl, Sebastian; Mallmann, Mathias; Strobel, Philipp; Schmidt, Peter J.; Schnick, Wolfgang
Abstract : The ortho ‐oxonitridophosphate Ba2 PO3 N was synthesized under ammonobasic conditions ( T = 1070 K, p = 120 MPa) in custom‐built high‐temperature autoclaves, starting from red phosphorus, BaO, NaN3 and KOH. Thus, single crystals of up to several hundred µm were obtained, which were used for single‐crystal X‐ray diffraction. Ba2 PO3 N [ Pnma (no. 62), a = 7.596(2), b = 5.796(1), c = 10.212(3) Å, Z = 4] crystallizes in the β‐K2 SO4 structure type with non‐condensed [PO3 N] 4– ions and is isotypic to its lighter homologues EA 2 PO3 N ( EA = Ca, Sr). Powder X‐ray diffraction, energy dispersive X‐ray and Fourier Transformed Infrared spectroscopy corroborate the crystal structure. The optical band gap was determined by means of diffuse reflectance UV/Vis spectroscopy to be 4.3 eV. Eu 2+ doped samples show green luminescence ( λ em = 534 nm, fwhm = 85 nm/2961 cm –1 ) when irradiated with UV light ( λ exc = 420 nm). However, Ba2 PO3 N:Eu 2+ shows strong thermal quenching, even at room temperature. Abstract : The ammonothermal method was used for synthesis of the ortho ‐oxonitridophosphate Ba2 PO3 N ( T = 1070 K, p = 120 MPa) using custom‐built high‐temperature autoclaves. In doing so, crystallites with sizes up to several hundreds of µm could be obtained. Eu 2+ doped samples show luminescence in the green region of the visible spectrum.